2022
DOI: 10.1063/5.0123981
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency backscattering properties of quasi-omnidirectional corner reflector: The great-icosahedral-like reflector

Abstract: The backscattering of perfectly conducting great-icosahedral-like reflectors is studied in the high-frequency domain. This particular faceted polyhedron, composed of 60 trihedral corner reflectors, is introduced to obtain closer omnidirectional backscattering. Due to the high cost of traditional methods, an estimation method for the full-polarized radar cross section is proposed, which is modified from the geometrical optics approximation method. The validity of the improved method is discussed, and its veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, electromagnetic wave is regarded as ray in GO method, hence the polarization effect of wave is ignored. In a previous research [21], we proposed a full-polarized RCS estimation method improved from GO, which is applicable to various complex corner reflectors, but the calculation process of this method is intricacy. For the specific OR structure, this paper modifies the response calculation of single reflection and double reflection to achieve a simple and fast full-polarized RCS estimation.…”
Section: Fast Methods Of Rcs Estimation For Ormentioning
confidence: 99%
See 1 more Smart Citation
“…However, electromagnetic wave is regarded as ray in GO method, hence the polarization effect of wave is ignored. In a previous research [21], we proposed a full-polarized RCS estimation method improved from GO, which is applicable to various complex corner reflectors, but the calculation process of this method is intricacy. For the specific OR structure, this paper modifies the response calculation of single reflection and double reflection to achieve a simple and fast full-polarized RCS estimation.…”
Section: Fast Methods Of Rcs Estimation For Ormentioning
confidence: 99%
“…As a premise, according to the relationship of polarization direction with the incident wave, parallel is defined as co‐polarization and orthogonal is defined as cross‐polarization. From the research [21] we have found that, in the case of single or triple reflection, the backscattering is completely co‐polarized. However, in the case of double reflection, it is possible that both co‐polarized response and cross‐polarized response would occur in backscattering, depending on the concrete aspect angles.…”
Section: Dynamic Sequential Rcs Calculation For Acr Arraymentioning
confidence: 99%
“…This requirement has been already investigated in many other radar studies. As a matter of fact, different structures able to backscatter the radar signal in many directions both in azimuth and in elevation have been produced and/or only simulated [14][15][16] . In the present study, three types of artificial reflectors (AR) with an effective target detectability in many directions have been investigated (Figure 4 RCS performances of the selected passive radar reflectors have been simulated considering different azimuth (φ) angles of incidence radar waves.…”
Section: Investigated Passive Radar Reflectors and Rcs Simulationsmentioning
confidence: 99%
“…In addition, corner reflector exhibits a number of advantageous properties with regard to scattering characteristics, spectral characteristics, polarization properties, and resistance to the technique of coherent accumulation. In recent years, the continuous advancement of structure and surface reflection materials has led to significant improvements in the performance metrics of corner reflectors, including coverage frequency bands, omnidirectionality, and the cost−effectiveness ratio of interference [2]. Consequently, many countries have devoted greater attention to the development of corner reflectors and deployed them in a variety of scenarios where they are used to counter the radar detection.…”
Section: Introductionmentioning
confidence: 99%